PWE-093 Early Outcomes of Bowelscope Screening (BoSS) Endoscopy & The Resulting Colonoscopies. (17th August 2016) - Gaglia, A; Fitzgerald, G; Hemer, S; Stewart, S; Duffy, U; O'Toole, P; Sarkar, S
Abstract : Introduction: Bowel scope screening (BoSS), a 1 off flexible sigmoidoscopy for 55 year olds, has recently been introduced as part of the Bowel Cancer screening in England. The outcomes & pathways of patients have been modelled around the landmark Atkins study and the long term effectiveness of the program will need time to be confirmed. The aim of this study was to review our early experience of the outcomes from BoSS including adenoma detection rate (ADR) and additional findings from colonoscopies following BoSS. Methods: This was a retrospective study reviewing our BoSS outcomes from the start of BoSS programme from March 2015 to January 2016. This included detailed outcomes of the colonoscopies generated from BoSS. Results: Over the 10 months of the study 658 BoSS were performed. The ADR was 11%. A total of 29 colonoscopies were generated with a conversion rate of 4.4%. Referral Patterns : When reviewing the referral patterns (21 male patients, 8 females), 7 could be considered inappropriate (24%) either because of over estimation of initial polyp size (n = 3; 10% were actual polyp size below 10 mm) or misdiagnosis of histology (n = 4; 14%> Histology hyperplastic). Of the appropriate referrals, 11 were due to polyps >1 cm (38%)(low risk), 5 (17%) were due to post polypectomy histology -high grade dysplasia and tubovillous (high risk), 4 (14%)were due to polyp >1 cm plus 2 or more adenomas (high risk), one was due to >20 hyperplastic polyps above the rectum and one was due to impossible polypectomy due to poor bowel preparation. Colonoscopic Findings : Of the 7 inappropriate referrals, 6 had only left sided pathology (85%), already diagnosed during BoSS and 1 (15%) had a 4 mm adenoma in the caecum. Of the appropriate referrals 14 of 22 (64%) had only left sided pathology detected. The median size was 6 mm (range 2–45 mm). 8 of 22 (36%) had right sided adenoma; median size 3 mm (range 2–12 mm), of which 4 were referred due to high risk adenomas, 3 due to low risk adenomas, and 1 due to more than 20 hypeplastic polyps above the rectum. Advanced Pathology : Interestingly, the most advanced adenomas in all colonoscopies but one, were the ones visualised at the sigmoidoscopy. One case with a 6 mm tubovillous adenoma in sigmoid had a 12 mm tubulous adenoma in the caecum. 1/22 cases had a 25 mm adenocarcinoma in the rectum. Conclusion: Our early experience suggests that whilst ADR within the programme is almost double the recommendation, it is important to remain within the pathway in view of the yield of pathology generated which will improve with on-going experience and education. No predictive factor was found for right colon lesions. It is reassuring that the most advanced lesions were the one visualised at the sigmoidoscopy. Disclosure of Interest: None Declared